(untitled) (CAHIERS MAGELLANES-NS, 2024)
This systematic review aimed to evaluate various approaches to guided bone regeneration (GBR) in implant dentistry using collagen membranes and particle grafting materials. A meta-analysis was conducted on studies published between 2001 and 2023, including prospective controlled research and randomized clinical trials. Main outcomes included survival rates, membrane exposure rates, bone gain/defect reduction, and vertical bone loss. Ten studies met the inclusion criteria. The rates of implant survival were comparable between simultaneous and later implant placement. Cross-linked membranes had a higher membrane exposure rate compared to non-cross-linked membranes. Membrane cross-linking, timing of implant placement, membrane fixation, and decortication were identified as influential factors on outcomes.